Effect of Propylene Glycol and Polyethylene Glycol with Molecular Weight of 1,500 on Erythrocyte Membrane Microviscosity - Nardid, Oleg A.; Cherkashina, Yana O.; Ivanov, Leonid V.; Nardid, Eduard O.; Lyapunov, Aleksandr N.; Mamontov, Vladimir V. (Problems of Cryobiology and Cryomedicine, 2016)
Electron paramagnetic resonance of spin probes was used to study the effect of low and high molecular weight CPAs on microviscosity of erythrocyte membranes. Research data on rotational mobility of the fatty acid spin probes in erythrocyte membranes after 5 min incubation in 15 % propylene glycol solution indicate the absence of strong changes in membrane microviscosity. Introduced polyethylene glycol with m. w. 1500 (PEG-1500) at a final concentration of 15% has been shown to increase the membrane microviscosity at 60 min exposure. This is explained by the fact that the molecules of PEG-1500 do not pass inside the cells and are localized on the membrane surface to cause immobilization and inhibiting the rotational mobility of the spin probe. In the initial period of time under these concentrations of PEG-1500 the injury of liquid crystal membrane structure and disorder of the protein-lipid interactions in the membrane prevail over the dehydration of cells. Probl Cryobiol Cryomed 2016; 26(1):35-44.